An Outline of Strategies for Building an Innovation System for Knowledge City - Crane, Keith (RAND Corporation, 2012)
Sino-Singapore Guangzhou Knowledge City is a planned environmentally and technologically advanced city in China's Guangzhou Development District that will host innovative industries and their workers. This report serves as an outline for a set of strategies for Knowledge City and is intended to help the developers create conditions that are conducive to innovation and the commercialization of new technologies.